PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA DENGAN PENDEKATAN CONTEXTUAL TEACHING LEARNING BERBASIS IMAN DAN TAQWA - Maielfi, Dini; Ratnawulan, Ratnawulan; Usmeldi, Usmeldi (Universitas Negeri Padang, 2012)
IMTAQ development in schools is very important as an effort to gain the educational goals according to the constitution No. 20 of 2003 Article 3 which states that education aims to develop students ability in order to be a faithful and cautious man to Almighty God and have a good behavior. Therefore it is necessary to develop learning tools that try to integrate the IMTAQ values in learning. Learning tools are very important for the teacher in order learning can run as expected. This research aims to develop physics learning tools with CTL approach based IMTAQ which is valid, practical and effective. This research is the development research which refers to the research and development by Borg and Gall consisting of 10 steps of research. In this research, those steps are modified in four stages, namely: 1) preliminary studies, 2) design of learning tools, 3) development of learning tools, and 4) application of learning tools. Data collection was conducted using validation and testing learning tools. The design of the learning tools that have been designed was validated by 4 validators then tested at the class XI MAN 2 Padang. The research results showed that 1) physics learning tools with CTL approach based IMTAQ that developed had been valid with some suggestions and improvements from the validator, 2) physics learning tools with CTL approach based IMTAQ was very practical based on the observation of student’s activities, and the questionnaire responses of teachers, 3 ) physics learning tools with the CTL approach based IMTAQ has been effective based on learning outcomes and assessment of students IMTAQ. In general, physics learning tools with CTL approach based on IMTAQ have been already valid, practical, and effective to be used in learning. This learning tools can support the learning process and integrate the values of IMTAQ in learning.